2019
DOI: 10.1186/s12917-019-2151-y
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and metabolic profiles in female dogs with mammary carcinoma receiving dietary fish oil supplementation

Abstract: BackgroundDyslipidemias induce angiogenesis and accelerate the development and in vitro growth of breast tumors. The aim of this study was to assess the lipid and metabolic profile of female dogs with mammary carcinomas and their correlations with body condition score and degree of tumor malignancy, as well as to study the effect of dietary fish oil supplementation on these animals.ResultsOverweight or obese dogs had more aggressive carcinomas and higher triglyceride (p = 0.0363), VLDL (p = 0.0181), albumin (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
1
8
0
1
Order By: Relevance
“…Acute respiratory failure was identified as the cause of death. Considering the cause of death and the presence of late metastases, similar results were described by Costa-Santos et al [ 25 ]. In the current study, the histological analyses of the affected organs confirmed the presence of metastases.…”
Section: Discussionsupporting
confidence: 83%
“…Acute respiratory failure was identified as the cause of death. Considering the cause of death and the presence of late metastases, similar results were described by Costa-Santos et al [ 25 ]. In the current study, the histological analyses of the affected organs confirmed the presence of metastases.…”
Section: Discussionsupporting
confidence: 83%
“…An estimated 34–59% of pet dogs in developed countries are overweight or obese [ 3 , 9 , 101 , 102 , 103 , 104 ]. Multiple comorbidities are associated with canine obesity, most notably: orthopaedic disease, exacerbation of breathing difficulties, and urinary incontinence, along with significantly decreased life expectancy [ 105 , 106 , 107 , 108 ]. Canine obesity is associated with increased blood pressure, dyslipidaemia, and insulin resistance, and this has been characterised as “obesity-related metabolic dysfunction” [ 109 , 110 ].…”
Section: Canine Obesity Geneticsmentioning
confidence: 99%
“…An estimated 34-59% of pet dogs in developed countries are overweight or obese [3,8,[88][89][90][91]. Multiple comorbidities are associated with canine obesity, most notably orthopaedic disease, exacerbation of breathing difficulties and urinary incontinence, along with significantly decreased life expectancy [92][93][94][95]. Canine obesity is associated with increased blood pressure, dyslipidaemia and insulin resistance and this has been characterised as 'obesity-related metabolic dysfunction'.…”
Section: Canine Obesity Geneticsmentioning
confidence: 99%